Perancangan Kincir Air Undershot Sebagai Penggerak Awal Pompa - Endang Prihastuty; Hary Dwi Harsono (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2019)
Moving water holds enormous natural energy. The energy that water has can be used as a drive for waterwheels or water turbines. The use of waterwheels can be used as the initial driver of the pump. Where the pump will raise water from the river to the higher ground. In Cipager village, Cirebon district has a Cipager river that has a heavy flow. With such river conditions, the energy owned by the Cipager River can be used to move the waterwheel which is then used as the initial driver of the pump. Without using electricity, villagers can use pumps to raise water from the river to higher ground. So that water needs can be met both for irrigating rice fields or fulfilling daily needs. The use of waterwheel as the initial drive of the pump needs good design and adapted to the conditions of the river flow. Data on the Cipager river condition with a flow velocity of 2.027 m / s and flowrate of 1850 L / s. for the design criteria selected undershot waterwheel. It was obtained for the size of the pinwheel design, 80 cm diameter, 12 cm blade length, 10 cm blade width with flat blade shape, 2 mm thick steel plate material and 2 mm shaft material. The windmill rotation was obtained at 48.34 rpm, the wheel power was 197.882 watts and the wheel weight was 58.8 N. While the power of the wheel used to drive the pump was only 5.18% of the total power of the windmill produced